2003
DOI: 10.1177/10598405030190030601
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assurance in School Health

Abstract: School nurses need to become more influential administrators, managers, and entrepreneurs. They must learn to lead and collaborate effectively in designing, implementing, and evaluating coordinated school health programs. Quality assurance is an essential ingredient in this process that requires accurate, timely, and confidential incident reporting and data analysis structures. These structures, in turn, can serve as the foundation of evidence-based practice and overall system improvement. School nurses can an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Poor understanding of the school nurse's role (Newell et al, 2003;Rice et al, 2005;Merrel et al, 2007;Buckley et al, 2009;Smith & Firmin, 2009), and a lack of understanding of professional responsibilities and legal requirements of nursing professionals (Newell et al, 2003;Rice et al, 2005;Broussard, 2007;Smith & Firmin, 2009;Sendall et al, 2011), are the most commonly identified challenges discussed in school nursing literature internationally.…”
Section: Key Challenges Of the School Nursing Rolementioning
confidence: 99%
“…Poor understanding of the school nurse's role (Newell et al, 2003;Rice et al, 2005;Merrel et al, 2007;Buckley et al, 2009;Smith & Firmin, 2009), and a lack of understanding of professional responsibilities and legal requirements of nursing professionals (Newell et al, 2003;Rice et al, 2005;Broussard, 2007;Smith & Firmin, 2009;Sendall et al, 2011), are the most commonly identified challenges discussed in school nursing literature internationally.…”
Section: Key Challenges Of the School Nursing Rolementioning
confidence: 99%
“…(2002) would, presumably, concur with this, as they offer insight into a successful Finnish HPS programme that was not only action research orientated, but nurse directed as well. Furthermore, for school nursing to progress, Newell et al. (2003) also put forward recommendations that its school nurses will need to develop key roles as senior administrators and mangers to lead and heavily influence coordinated school health programmes.…”
Section: Developing the School Nursing Role Further?mentioning
confidence: 99%